2018
DOI: 10.1002/jcla.22714
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of severity in acute ischemic stroke and transient ischemic attack using platelet parameters and neutrophil‐to‐lymphocyte ratio

Abstract: Background It is still not easy to predict severity promptly in patients with acute ischemic stroke (AIS) and transient ischemic attack (TIA). We investigated that platelet parameters or combinations of them could be a useful tool for early prediction of severity of AIS and TIA at admission and after 3 months. Methods We prospectively recruited 104 patients newly diagnosed with AIS and TIA. We investigated their neutrophil‐to‐lymphocyte ratio (NLR) and platelet parameters. According to the Modified Rankin Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Furthermore, elevated D-dimer and hyperfibrinogenemia, which are both biomarkers of inflammation and hypercoagulable state, have also been shown to predict the severity of the said infection (31,32). Interestingly, similar biomarkers predict outcomes in stroke (33)(34)(35)(36)(37)(38)(39). In particular, it is known that patients who show elevated NLR, ferritin, CRP, D-dimer and fibrinogen have a higher risk for stroke and equate to potentially poorer clinical outcomes (33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elevated D-dimer and hyperfibrinogenemia, which are both biomarkers of inflammation and hypercoagulable state, have also been shown to predict the severity of the said infection (31,32). Interestingly, similar biomarkers predict outcomes in stroke (33)(34)(35)(36)(37)(38)(39). In particular, it is known that patients who show elevated NLR, ferritin, CRP, D-dimer and fibrinogen have a higher risk for stroke and equate to potentially poorer clinical outcomes (33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…NLR has been identified to be a useful clinical predictor of outcome in AIS patients being considered for mechanical thrombectomy, as NLR can predict functional dependence and mortality after adjustment for potential confounders that included vascular risk factors. Multiple analyses reveal NLR correlates with a greater functional disability at admission and at three months (increased mRS and NIHSS scores) and increased 90-day mortality (21)(22)(23)(24)(25)(26)(27) and was furthermore associated with length of hospital stay (28) and cost (29). Patients with NLR >3.3 were 2-times more likely to be at risk of death (24).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several of these studies have combined AIS and TIA into a single group for comparison. For example, Ross et al and Lim et al compared immune cell counts between AIS and TIA versus control, and while both studies reported significantly increased neutrophil percentage and decreased lymphocyte percentage in AIS and TIA compared to control, neither of these studies compared AIS to control [ 3 - 4 ]. Gökhan et al reported that the neutrophil count and neutrophil-lymphocyte ratio (NLR) were significantly higher in AIS compared to TIA [ 5 ].…”
Section: Introductionmentioning
confidence: 99%